Analysis of precision machined surfaces - Liu, Na. (2008)
In this disserlation, the research work is on analysis of precision machined surfaces. Firstly, current major precision machining methods are reviewed and main surface characteristics are discussed. Secondly, important theories used in the experiment and the analysis method are presented. They are sampling length, design of experiments and ANOVA. Thirdly, two schemes of the experiment are described. Two measurement instruments are used. The schemes are designed to be randomized. In other words, every measurement is independent.